Hubungan Dukungan Sosial Keluarga dengan Resilience Penderita TB Paru di Wilayah Puskesmas Jatirahayu Kota Bekasi - Barkah, Asep; Aini, Nurul (Universitas Malahayati, 2025)
ABSTRACT WHO data, (2023) shows that around 1.30 million deaths are caused by TB. The number of people newly diagnosed with TB globally is 7.5 million. Most TB cases are in Southeast Asia (45%), Africa (24%) and the Western Pacific (17%). In 2023, the highest contributors to pulmonary TB cases globally will be India (26%), Indonesia (10%), China (6.8%). The highest prevalence of pulmonary TB in Indonesia is in Central Papua Province at 1.15%, the second is in South Papua at 0.98% and the third is Mountain Papua at 0.77%. Meanwhile, the prevalence of pulmonary TB cases in West Java is 0.47%. In order for someone suffering from TB to be able to fight the anxiety and fear caused by their disease, they need love and attention from the people around them. Knowing the relationship between family social support and the resilience of pulmonary TB sufferers. Analytical with cross sectional design. The sample in this study was a portion of pulmonary TB patients in the Jatirahayu Bekasi Community Health Center area in January 2025, totaling 50 respondents. The sampling technique uses random sampling. Most pulmonary TB sufferers receive good family support (76.0%) and moderate resilience (40.0%). There is a relationship between family social support and the resilience of pulmonary TB sufferers in the Jatirahayu Community Health Center Area, Bekasi City (p. value 0.003). There is a relationship between family social support and the resilience of pulmonary TB sufferers in the Jatirahayu Community Health Center Area, Bekasi City. It is hoped that health workers can improve and develop nursing plans regarding family social support and resilience for pulmonary TB sufferers. Keywords: Family Social Support, Resilience, Pulmonary TB ABSTRAK Data WHO, (2023) menunjukkan sekitar 1,30 juta kematian disebabkan oleh TBC. Jumlah orang yang baru didiagnosis TBC secara global adalah 7,5 juta. Sebagian besar kasus TBC berada di Asia Tenggara (45%), Afrika (24%) dan Pasifik Barat (17%). Pada tahun 2023, penyumbang kasus TB paru tertinggi secara global adalah India (26%), Indonesia (10%), Tiongkok (6,8%). Prevalensi TB paru di Indonesia tertinggi berada di Propinsi Papua Tengah sebesar 1,15%, yang kedua di Papua Selatan sebesar 0,98% dan urutan ke tiga yaitu Papua Pegunungan sebesar 0,77%. Sedangkan prevalensi kasus TB paru di Jawa Barat sebesar 0,47%. Agar seseorang penderita TBC mampu melawan rasa cemas dan takut akibat penyakitnya, mereka membutuhkan cinta kasih serta perhatian dari orang-orang yang ada di sekitarnya. Mengetahuihubungan dukungan sosial keluarga dengan resilience penderita TB paru. Analitik dengan rancangan cross sectional. Sampel dalam penelitian ini adalah sebagian pasien TB paru di Wilayah Puskesmas Jatirahayu Bekasi pada bulan Januari 2025 sebanyak 50 responden. Teknik pengambilan sampel menggunakan randoom sampling. Sebagian besar penderita TB paru mendapatkan dukungan keluarga baik (76.0%) dan resilience sedang (40,0%). Ada hubungan dukungan sosial keluarga dengan resilience penderita TB Paru di Wilayah Puskesmas Jatirahayu Kota Bekasi (p. value 0,003). Ada hubungan dukungan sosial keluarga dengan resilience penderita TB Paru di Wilayah Puskesmas Jatirahayu Kota Bekasi. Diharapkan tenaga kesehatan dapat meningkatkan dan dapat mengembangkan perencanaan keperawatan tentang dukungan sosial keluarga serta resilience penderita TB paru. Kata Kunci: Dukungan Sosial Keluarga, Resilience, TB Paru.